Mohammadiah’s Moderation Concept In The Implemetation of Multicultural Nivels - Fatimah, Tri Putri Siti; Hafiz, Hafiz (Universitas Muhammadiyah Surakarta, 2024)
Indonesia is a country that has a lot of diversity, not only in cultural diversity but also in religious diversity; each religion alone still has some differences. While Muhammadiyah was one of the organizations that was founded in Indonesia in 1912 and founded by K.H. Ahmad Dahlan in Yogyakarta, Mohammadiyah is also one of those organizations that has a moderate concept in addressing the problems of diversity that exist. Multiculturalism is diversity in a very broad context, discussing the multiculturalism of Muhammadiyah as one of the organizations that is concerned with all such matters. Using qualitative research methods and gathering data from library studies, this article will discuss the concept of Muslim moderation in enhancing multicultural values. The gathered data will be presented in a brief descriptive manner in this article. The Prophet (peace and blessings of Allah be upon him) said: “Because Allah is not pleased with such a thing, he has taught his people not to bow down to one thing”. With the stubbornness of the founder of Muhammadiyah, K.H. Ahmad Dahlan, Muhammadiyah finally has the concept of moderation to capture the diversity that exists in this country, ranging from cultural diversity to the diversity in Bergamot and also the variety in Bermazhab.